Prophylaxis and Post-exposure Treatment of Intoxications Caused by Nerve Agents and Organophosphorus Pesticides - Kuca, Kamil; Jun, Daniel; Musilek, Kamil; Pohanka, Miroslav; Zdarova Karasova, Jana; Soukup, Ondrej (Mini Reviews in Medicinal Chemistry, 2013)
Treatment of intoxications caused by nerve agents and organophosphorus pesticides consists of different approaches. The first approach is called prophylaxis or pre-exposure administration of antidotes such as cholinesterase reactivators or bioscavengers. The second, post-exposure treatment consists of anticholinergic drugs, acetylcholinesterase reactivators and anticonvulsants. This article is aimed at both mentioned approaches, especially focused on cholinesterase reactivators, which are a broad group of structurally different compounds that can be used in prophylaxis (separately or in combination with butyrylcholinesterase) and also as post-exposure treatment.
Keywords: nerve agents